Crystal structure of ethylenediaminesilver(I) 4-nitrobenzoate hemi-hydrate, Ag(C2H8N2)(C7H4NO4) · 0.5H2O - Zhu H.-L. (Zeitschrift für Kristallographie - New Crystal Structures, 2003)
C9H13AgN3O4.50, monoclinic, C12/c1 (No. 15), a = 8.331(2) Å, b = 11.645(2) Å, c = 23.947(5) Å, β = 94.845(3)°, V = 2314.8 Å3, Z = 8, Rgt(F) = 0.030, wRref(F2) = 0.072, T = 298 K.